Early postnatal development of the immune system in piglets: the redistribution of T lymphocyte subsets - Stepanova, H; Samankova, P; Leva, L; Sinkora, J; Faldyna, M (Cellular immunology, 2007)
In this study, we have characterised postnatal changes in T lymphocyte subsets, especially gammadelta T lymphocytes, in blood, spleen and lymph nodes. Detection was carried out using two-colour flow cytometry and three-colour immunohistochemistry. During ontogeny, there was a significant increase in the total percentage of gammadelta T cells in the spleen and blood. In the lymph nodes, there were no age-dependent changes in the total percentage of gammadelta T cells, but the percentage of the gammadeltaTCR+CD8+ subpopulation significantly increased. The tissue distribution of gammadeltaTCR+CD8+ and gammadeltaTCR+CD8- cells in the lymph nodes is random and not collocated with a particular area of the organ. Furthermore, postnatal development was characterised by an increasing frequency of CD8+CD3+CD4-gammadeltaTCR-, which was compensated by a decreasing proportion of CD4+ lymphocytes. Double positive CD4+CD8+ lymphocytes were rare during the first month of life and a significant age-dependent increase of these cells was found in all the compartments monitored.
Keywords: Swine; T-Lymphocyte Subsets; novorozená zvířata; průtoková cytometrie; Animals, Newborn; lymfoidní tkáň; Animals; Immune System; Receptors, Antigen, T-Cell, gamma-delta; receptory antigenů T-buněk gama-delta; Flow Cytometry; Lymphoid Tissue; zvířata; Immunohistochemistry; prasata; T-lymfocyty - podskupiny; imunitní systém; imunohistochemie